Sport as Therapy - Fichtner A; 3; Chekhanova A; Wuensche A; Starkloff HJ; Fieback T; Koch T (Deutsche Zeitschrift für Sportmedizin, 2021)
Introduction: Sufficient hydration of a SCUBA diver is important to reduce the risk of decompression sickness. Mechanisms of fluid loss in diving and immersion are known, but not quantified. We aimed at relating dive profiles and individual parameters to fluid loss in order to develop an estimation of necessary amount of fluid restoration between dives.Methods: 41 SCUBA divers with a broad spectrum of ages, sex, and bio data performed 342 single and repetitive dives on air in an open breathing system. Before and after the dives, body weight, bio data and dive profiles were recorded.Results: Average dive profile was 22.9 meters and 46.5 minutes, average weight loss was 0.8 kg after repetitive dives and 1.0 kg (1.2% relative body weight) after the first dive of the day. Significant correlations were found between relative weight loss and a single dive (no repetitive diving), younger age, dive time, non smoking, body weight and lean body mass. No significant correlation was found for air consumption, fluid intake, circulatory parameters, bio data, water temperature, and salinity.Discussion: Immersion-induced individual physiological responses are the major mechanisms leading to fluid loss in divers, since correlation with dive and biometric parameters is low. Except for small contribution from humidification of dry breathing gas, dive parameters are not suitable to determine necessary fluid replacement. Only a rough estimate of 1 liter per standard sports dive is possible.Key Words:Inert Gas Solution, Dehydration, Decompression, Immersion